RC-based oscillator for RF-applications - Sebastian Beier (2017)
In sub-micron CMOS processes LC-oscillators require considerable amount of area because of the integrated inductor. To decrease the die size and to reduce the magnetic field intensity (H-fields) disturbances it can be useful to use a RC-oscillator instead of a LC-oscillator. This work describes the basic function of a Cross-Coupled- RC-Oscillator in 65nm RF CMOS technology. Furthermore, the transfer function as well as the dimensioning for the oscillator for a minimal specified value of phase noise will be given. It is a combination of theoretical views, assumptions and simulations. The simulation results shall confirm the theoretical part as well as the calculation of the component parameters where needed. The summary and a proposal for next steps will complete this work.
Keywords: RC Oszillator; Relaxation Oszillator; quasi lineares Verhalten; Phasenrauschen; RC oscillator; relaxation oscillator; quasi linear behavior; phase noise